Bi nanowires modified by 400 keV and 1 MeV Au ions - Guerra, D.B. (2022)
We report on the modification of the structure and morphology of Bi nanowires of two different diameters (80 or 130 nm) exposed to beams of 400 keV and 1 MeV Au+ until complete wire degradation. For fluences up to ∼1 ion/nm2 , the main effect was a slight roughening of the originally smooth surface and the appearance of a damaged zone at the wire edges. After an exposure to ∼2 ions/nm2 , shallow (∼5-7 nm deep) but wide (up to 120nm) depressions are seen, giving the wires a “wavy” morphology. At the largest fluence tested (10 ions/nm2 ), the thickest nanowires present an amorphized structure containing an embedded dispersion of small spherical metallic crystallites, while the thinner wires collapse into large (∼50nm) nanoparticles composed of a crystalline core surrounded by a disordered oxidized shell. The observed morphologic modifications are discussed considering sputtering and radiation induced surface diffusion effects.